2013
DOI: 10.11118/actaun201260060089
|View full text |Cite
|
Sign up to set email alerts
|

Use of G-phase for biogas production

Abstract: Biogas is very promising renewable energy resource. The number of biogas plants increase every year. Currently there is a demand for new ways of organic waste treatment from production of different commodities. One of the technologies which produce waste is biodiesel production. One of the wastes from the biodiesel production is G-phase which is mainly consisted from glycerol and methanol. The aim of work was to find the effect of G-phase addition, to fermented material, on biogas resp. methane production. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…compost. Its beneficial effects have already been proven in anaerobic reactors, as reported by Orrico Jr. et al (2016) and Haitl et al (2012), who used glycerin in the substrates and found greater breakdown of the solids contents during the digestion process, besides higher biogas and methane productions. Nonetheless, few studies are available on composting.…”
mentioning
confidence: 75%
“…compost. Its beneficial effects have already been proven in anaerobic reactors, as reported by Orrico Jr. et al (2016) and Haitl et al (2012), who used glycerin in the substrates and found greater breakdown of the solids contents during the digestion process, besides higher biogas and methane productions. Nonetheless, few studies are available on composting.…”
mentioning
confidence: 75%
“…Thermodynamic analysis is dealt with in the article (Chawla, Ghost 1992), where the calculation of parameters in generating hydrogen from biogas for fuel cells is described. Production of gaseous components in biofuel combustion is studied also in the work (Jandačka et al 2011;Haitl et al 2012). Usage of biogas as a fuel for combustion engines is described in the work of (Jablonický et al 2010).…”
Section: Characteristic Indicatorsmentioning
confidence: 99%
“…The article analyses methods of biogas production from rye grass. Biogas production from other materials is examined in the works of (Haitl et al 2012;Janíček et al 2012;Zhang et al 2015) and others. Diversity, which is apparent in the biogas composition, can be also found in the methods of determination of the necessary parameters.…”
Section: Characteristic Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Glycerol and Methyl wash water are good in methanol content. So the production of biogas from these by-producers is possible [4].The biogas can be produced by Anaerobic digestion which will breakdown Impact Factor (JCC):6.8765 NAAS Rating: 3.11…”
Section: Introductionmentioning
confidence: 99%